Plants Used in the Nyadran Tradition: An Ethnobotanical Study in Balongdowo Village, Sidoarjo, Indonesia - Hesti Aristrias Zena; Nurul Istiqomah; Adisty Revyna Susanto; Muhammad Rafif Aditya; Karin Anindita Widya Pitaloka; Fahrul Ghani Muhaimin; Susriyati Mahanal (Pro-Life, 2026)
Biodiversity plays an important role in supporting cultural practices and tradition within local communities, where various plant species are utilized not only for practical purposes but also for symbolic and spiritual meanings embedded in cultural rituals. This study aims to document and preserve the Balongdowo community's local ethnobotanical knowledge of plant use in the Nyadran tradition. The research was conducted through observation, structured interviews with key informants, documentation, and literature review. Data were analyzed descriptively following the stages of data collection, reduction, presentation, and conclusion drawing. The results show that the Nyadran tradition involves various plant species used as components of offerings, ritual equipment, and symbolic elements. Nine plant species were identified, including pisang (Musa spp.), pandan (Pandanus amaryllifolius), padi (Oryza sativa), krisan (Chrysanthemum sp.), melati (Jasminum sp.), kenanga (Cananga odorata), champaca (Magnolia champaca), kamboja (Plumeria sp.), and mawar (Rosa damascena). Each plant has a specific philosophical meaning related to fertility, purity, protection, gratitude, and spiritual connection with ancestors. The use of fresh plant materials also reflects ecological values and local conservation practices. Plants are obtained from homegardens and markets, with most species categorized as Least Concern on the IUCN Red List. Community involvement, including women and youth, contributes to the preservation of cultural values and the sustainability of ritual plants. This study highlights the importance of ethnobotanical approaches in understanding human–plant relationships and supports the conservation of both cultural heritage and biodiversity within coastal communities.